2010
DOI: 10.1093/cercor/bhq071
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Architecture of the Infant Brain as Revealed by Resting-State fMRI

Abstract: The functional network topology of the adult human brain has recently begun to be noninvasively mapped using resting-state functional connectivity magnetic resonance imaging and described using mathematical tools originating from graph theory. Previous studies have revealed the existence of disproportionally connected brain regions, so called cortical hubs, which act as information convergence zones and supposedly capture key aspects of how the brain's architecture supports human behavior and how it is affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
354
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(406 citation statements)
references
References 66 publications
51
354
1
Order By: Relevance
“…Functional hubs were found to be predominantly confined to brain regions supporting primary functions (e.g. sensorimotor and visual cortex) and only a few hubs have been observed in association cortices including the insula and posterior cingulate cortex (De Asis-Cruz et al, 2015;Fransson et al, 2011;Gao et al, 2011). Notably, the configuration of functional brain hubs as observed in the neonatal brain is highly consistent with the outline of resting state networks during this period.…”
Section: Functional Connectomementioning
confidence: 67%
See 1 more Smart Citation
“…Functional hubs were found to be predominantly confined to brain regions supporting primary functions (e.g. sensorimotor and visual cortex) and only a few hubs have been observed in association cortices including the insula and posterior cingulate cortex (De Asis-Cruz et al, 2015;Fransson et al, 2011;Gao et al, 2011). Notably, the configuration of functional brain hubs as observed in the neonatal brain is highly consistent with the outline of resting state networks during this period.…”
Section: Functional Connectomementioning
confidence: 67%
“…A number of reports described functional network architecture in neonates on a whole-brain level (De Asis-Cruz et al, 2015;Fransson et al, 2011;Gao et al, 2011). In line with network attributes of the neonatal structural connectome and adult human brain organization, functional brain networks in newborn infants exhibit small-world topology, a modular organization and a heavy-tailed degree distribution with functional hubs (Box 1).…”
Section: Functional Connectomementioning
confidence: 99%
“…(e.g. Dudink et al, 2012;Fransson et al, 2011;Lodygensky et al, 2010). The next obvious advance will be to define the functional correlate of any altered structure, and this can only be accomplished with improved spatial EEG information.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in neuroimaging (Dudink et al, 2012;Fransson et al, 2011;Lodygensky et al, 2010) and in developmental neurobiology (Colonnese and Khazipov, 2012;Hanganu-Opatz, 2010;Vanhatalo and Kaila, 2010) has made it clear that brain functions are already highly specialized early in development. Functional assessment of neonatal brain activity is currently severely hampered by the poor spatial resolution provided by conventional neonatal EEG recording (Andre et al, 2010), which hardly suffices to distinguish brain lobes from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies have looked at functional network development in young infants [19,20,22,56]. Fransson et al, in particular, examined the resting-state functional network architecture of very young preterm infants (25 weeks mean gestational age) and found that only half of the number of resting-state sub-networks found in healthy adults were present at the preterm stage [20].…”
Section: Introductionmentioning
confidence: 99%